2012
DOI: 10.1073/pnas.1121077109
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for social working memory from a parametric functional MRI study

Abstract: Keeping track of various amounts of social cognitive information, including people's mental states, traits, and relationships, is fundamental to navigating social interactions. However, to date, no research has examined which brain regions support variable amounts of social information processing (“social load”). We developed a social working memory paradigm to examine the brain networks sensitive to social load. Two networks showed linear increases in activation as a function of increasing social load: the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
194
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 199 publications
(212 citation statements)
references
References 64 publications
(76 reference statements)
13
194
4
Order By: Relevance
“…For instance, increased activation of the mPFC has been found when a higher number of social targets have to be remembered (Meyer et al, 2012), when there are more targets in one's social network (Lewis et al, 2011), and when a higher level of abstractness is required in the representation of social targets (Baetens et al, 2014). Heightened activation for social categories compared to traits in the anterior temporal lobe also corresponds to findings that this region is involved in the retrieval and representation of abstract social semantic knowledge (Olson et al, 2013;Zahn et al, 2007).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…For instance, increased activation of the mPFC has been found when a higher number of social targets have to be remembered (Meyer et al, 2012), when there are more targets in one's social network (Lewis et al, 2011), and when a higher level of abstractness is required in the representation of social targets (Baetens et al, 2014). Heightened activation for social categories compared to traits in the anterior temporal lobe also corresponds to findings that this region is involved in the retrieval and representation of abstract social semantic knowledge (Olson et al, 2013;Zahn et al, 2007).…”
Section: Discussionmentioning
confidence: 69%
“…They have higher idiosyncratic, specific and complex representations, due to the higher number of individuals involved and the sometimes broad social categories they represent (e.g., woman). This higher complexity and variability may demand a higher level of information processing, leading to increased activation of the mentalizing network (Meyer et al, 2012;Mitchell, 2010). Lastly, social categories reflect a higher level of abstractness or construal (Trope and Liberman, 2010).…”
Section: Neurophysiological Findings On Social Categories and Traitsmentioning
confidence: 98%
“…However, there are few limitations that attention should be paid to in this study. For example, we failed to administrate any measure of memory, so it is difficult to rule out the possible effects of memory on reported results as of the role of DMN activation in social working memory Meyer, Spunt, Berkman, Taylor, & Lieberman, 2012) and the proposed part of memory in empathy (Beadle, Tranel, Cohen, & Duff, 2013) and prosocial behavior (Gaesser, 2012). As a result, it is reasonable to investigate the impacts of memory on the relations between perceived social support and DMN activations and connectivity in future studies.…”
Section: Discussionmentioning
confidence: 91%
“…Relationships theoretically impose a high load because of the large degree of interaction between their elements, their high emotional content and the fact that, unlike non-social WM tasks, their solution is often open-ended: there is no clear-cut Brightâ nswer (Goddard et al 1998;Kirschner 2002;Kron et al 2010;Paas et al 2003a). Indeed, recent research which focuses exclusively on social WM has found that, in contrast to conventional WM tasks, the processing of social tasks employs two networks-the medial frontoparietal region which is employed in social cognition (including mentalising tasks) and the lateral frontoparietal system which is usually employed in non-social WM tasksleading to a higher processing cost (Meyer et al 2012).…”
Section: Introductionmentioning
confidence: 99%